A Case of Penetrating Craniomaxillofacial Injury in the Time of COVID-19 - Baccay, Oliver Gabriel; Santos-Perez, Jesusa; Amable, Jay Pee (Philippine journal of otolaryngology head & neck surgery, 2025)
Objective: To describe a case of a craniomaxillofacial penetrating injury focusing on the importance of a multidisciplinary approach with insights into the surgical planning for successful removal of the foreign body during the pandemic. Methods:Design: Case ReportSetting: Tertiary Government Training HospitalPatient: One Results: A 15-year-old boy presented with a work-related puncture wound in the right nasomaxillary area with accompanying soft-tissue swelling. Physical examination of his face showed no external foreign body. Craniofacial computed tomography scans revealed a rodshaped opaque foreign body about 12 cm in length and 9 mm in diameter lodged in the right maxillary sinus extending to the right temporal lobe. The otolaryngology-head and neck surgeonand neurosurgeon planned the crucial extraction of the foreign body, but the requirement for a negative RT-PCR, blood products, and additional imaging delayed this emergent operation. The foreign body was eventually removed via combined trans-antral approach and right frontotemporal craniotomy, zygotomy, and craniectomy around the foreign body in the temporal floor with duraplasty and cranioplasty. Conclusion: Successful treatment of penetrating craniomaxillofacial injuries involves diligent clinical assessment, radiologic diagnosis and a well-planned multidisciplinary surgical approach. Delays in treatment may be beneficial if they allow precise location of the foreign body and thorough evaluation of involved structures. Safeguarding the healthcare workers during the pandemic was as important as ensuring a successful and safe surgery for the patient.